Khaya anthotheca (Welw.) C. DC. (Meliaceae) - An exotic species in Bangladesh - Alam, Md. Khairul; Basak, Sukla Rani; Alam, Syedul (Bangladesh Journal of Plant Taxonomy, 2012)
Not available. DOI: http://dx.doi.org/10.3329/bjpt.v19i1.10948 Bangladesh J. Plant Taxon. 19(1): 95-97, 2012 (June)